Pembangunan e-tutoran pemodelan 3 dimensi : satu pendekatan kreatif - Syadiah Nor Wan Shamsuddin
This research is: purposely to develop an e-tutor for learning and teaching of 3D modeling using theories and approaches that are relevance and the usage of multimedia elements in software can give dissimilarity and increase students' interests. Therefore the rationale of developing this E-tutor because most of elearning nowadays are not systematic and well structured and did not emphasize on theories and strategies of teaching and learning. The result of this research is a conceptual model from well research of literature review and a prototype of 3d modeling E-SITES courseware. The development of this E-SITES courseware consists of theories such as cognitive, constructivism, elaboration and andragogy. Creativity approach is also implemented to this software based on recent creativity models so that objects can be drawn creatively. Dick & Carey(1996) and IDI(1991) development model methodology are used in developing this courseware as a guideline. However, researcher had combine and made changes purposely for this development.Target users are students from higher learning institutions. E-SITES consists of several modules such as Tutorial Module, Task Module, Utility Module and Forum Module. It is emphasis on Tutorial Module that is consists of three levels: Basic, Medium and Complex that focus on 3d modeling from basic to complex based on Malay heritage such as keris, wau;. congkak, gong and rebana to nourish the valuable heritage so it will not be neglected by the time period. The learning and teaching of this software hopefully can help the learning of 3d modeling to be more creative and also the experiences will be more enjoy and effective.